The Development Enviromental Literacy Media Learning for Elementary School Student - Gusti Izhar; Kristi Wardani; Novian Kharisma Nugraha (Yayasan Keluarga Guru Mandiri, 2022)
Developing environmental literacy is a significant challenge for Indonesian education. A solid environmental caring character embedded in students can occur due to the success of environmental literacy education, so it is expected that students have a good understanding of the environment. The research aims to produce android-based mobile learning media about environmental literacy in elementary school thematic learning and test the feasibility of android-based mobile learning media developed. This research using research and development (RD) methods, has stages: 1) Analyze, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. Research place in SD Negeri 2 Pagedangan. Research data is processed using instruments. Data analysis techniques are carried out in a quantitative descriptive way. Media eligibility is based on material and media experts' assessments. The results showed that the resulting android-based mobile learning media was worth using with an average score of 3.42 with an